Prevalence and Risk Factors of Metabolic Syndrome Among Teaching Staff of Engineering Colleges in Central India - Sanjay, Agrawal; Sanjeev, M. Chaudhary; Sanjay, S. Kubde; Manjusha, Dhoble; Moin, Shaikh (Journal of Preventive Medicine And Care, 2020)
Background Prevalence of Metabolic syndrome is high among Asians including Indians, and is high among those having sedentary occupations. Teaching is one of the important occupations, which demands no strenuous physical activity. However, there is little information available about the prevalence of metabolic syndrome among teaching staff of engineering college. Hence, the present study was conducted to study its prevalence, certain risk factors and co-morbidities among teaching staff of engineering institutes. Methods Teachers from engineering colleges of Nagpur city were the study subjects. Data was collected by interview technique. Clinical examination and laboratory investigations like Fasting blood glucose, High Density Lipoproteins and Serum Triglycerides were done. National Cholesterol Evaluation Programme (NCEP) Adult Treatment Panel Three (ATPIII) criteria were used to study Metabolic syndrome. Blood pressure and anthropometric measurements like height, weight and waist circumference were obtained by standard methods. Results The prevalence of metabolic syndrome was found to be 20.5%. It was 25.32% in females and 19.31% in males. It was more common in subjects of higher age group, muslim religion, and among widows and separated. Alcohol consumption, smoking and sedentary life style was found to be significantly associated with presence of metabolic syndrome. Frozen shoulder, fungal infection and stroke were common co morbidities found among subjects having metabolic syndrome.
Keywords: Metabolic syndrome; engineering teacher; co-morbidity; physical inactivity